Flujo sanguíneo y transporte de oxígeno en los vasos capilares - Escobar del Pozo, Carlos (My University, 2008)
Flujo sanguíneo y transporte de oxígeno en los vasos capilares
Keywords: Flujo sanguíneo y transporte de oxígeno en los vasos capilares